(untitled) (Al Insyirah International Scientific Conference on Health, 2021)
Patient satisfaction is the main indicator of the quality of hospital services as well as a measure of service quality. The purpose of the research is to analyze of BPJS inpatient satisfaction in BLUD RSUD Jampangkulon Sukabumi. The methodology uses descriptive analysis with a cross-sectional design. The number of samples as many as 110 respondents obtained from the Hypothesis test formula with two different proportions. Primary data collection techniques using questionnaires, interviews and observations. Validity test with the Pearson Product Moment formula and reliability test with Cronbach Alpha. Data analysis using Logistic Regression Analysis and Cartesian Analysis. The results showed that the majority of patients said they were satisfied with the service in general at 94.5%, as well as based on the dimensions of service quality. The variables that were significantly related to patient satisfaction were tangible, reliability, empathy, and the most dominant variable affecting patient satisfaction was responsiveness with the highest OR, namely 50.39. In terms of patient expectations and satisfaction, the main priority for improvement is the accuracy of the examination schedule, the speed with which doctors respond, complete drug supplies, complete medical equipment and cleanliness of the room. It is hoped that the hospital management will improve its top priorities and make efforts such as providing clarity of service information, fast service and availability of prioritizing the interests of patients as an effort to improve the quality of services in the BLUD RSUD Jampangkulon Sukabumi, Sukabumi Regency